Endozoochorous seed dispersal and germination strategies of Serengeti plants. (1st August 2013) - Anderson, T. Michael; Schütz, Martin; Risch, Anita C.; Bruun, Hans Henrik
Abstract Questions How do rates of endozoochory change across gradients of environmental variation, grazing intensity and herbivore body size? Is there evidence that plants experience a trade‐off in successful germination in dung vs soil, and if so, are opposing strategies associated with traits indicative of evolutionary grazing history? Location Serengeti National Park, Tanzania and a greenhouse in Birmensdorf, Switzerland. Methods We compared rates of seedling emergence from the dung of six grazing herbivore species and soil collected across an environmental gradient in the Serengeti; we experimentally exposed both dung and soil to smoke to test for the effects of breaking seed dormancy. We analysed overlap in plant composition of seedlings germinated from dung and soil and asked whether species found in dung (but not soil) or soil (but not dung) differed in traits that are associated with evolutionary grazing history, such as leaf height and seed head height. Results Spatially, dung samples collected in the heavily grazed Serengeti plains contained more seeds than more northern sites. Median seedling emergence from dung varied among herbivores: hartebeest and wildebeest had the most, topi and zebra had intermediate numbers and Thomson's and Grant's gazelle the fewest, with Grant's gazelle dung being composed almost entirely of herbaceous dicots. Smoke failed to induce a germination response when applied to dung, but the composition of plant species germinating in 'dung only' or 'soil only' was surprisingly distinct. Moreover, seed head heights and leaf heights were shorter for plant species that germinated from dung compared to those that germinated from soil. Finally, the abundance of seeds germinating in dung and soil showed opposite patterns across the transition from short‐grass, historically grazed sites in the south to tall‐grass, fire‐prone sites in to the north. Conclusions Together, our results suggest that some Serengeti plant species may be specialized to disperse via the dung of large herbivores. Consequently, endozoochory may be an important, and thus far overlooked, ecological process in Serengeti and in tropical savannas dominated by large herbivores more generally.